Pandangan Abul A’la Al Maududi tentang Negara Islam - Nurlidiawati, Nurlidiawati (Rihlah: Jurnal Sejarah dan Kebudayaan, 2014)
This paper explore Abul A’la al-Maududi’s thought of Islamic nation. he was eager to realize the Islamic government because he wants the Muslims as a whole run the government in accordance with the instructions of the Koran holy book and ordinances as well as the implementation of the rules as they never practiced by the Prophet. Sovereignty is in God, the laws in force must be based on Islamic shariah. The ideas of Maududi of an Islamic state foundation on leadership Khulafa al-Rashidun.